Principles of web design - Sklar, Joel (Cengage Learning, 2015)
Beginning with the web design environment and the principles of sound web design, students will continue to planning site layout and navigation, and progress to web typography, colors and images, and more. With thought-provoking hands-on activities and projects, students will gain a solid foundation of designing successful, standards-based, responsive web sites that are portable across different operating systems, browsers, smartphones and tablets